(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
The article discusses ways of understanding the essential characteristics of media education in the context of training foreign language specialists, it is necessary to refer to the functions, features and types of mass media (mass media – further) and how develop of media literacy and communicative competence in English classes in non-linguistic universities.